Reinforcement Pendidikan Islam melalui Program Gerbang Salam di Pamekasan - supandi, supandi; M. Sahibudin; Moh. Wardi; Ismail (TADRIS: Jurnal Pendidikan Islam, 2021)
What we mean by Islamic education is the implementation of educational activities carried out in the implementation of education in general, namely formal and non-formal Islamic education or community-based Islamic education based on the Islamic Community Development Movement program which was later termed (Gerbang Salam) which was carried out in Pamekasan Regency. The term "Gate Salam" first appeared in Pamekasan Regency in 2010 based on the passion of the Pamekasan community. Together with community leaders and ulama' who have the same desire, namely to create a society that is based on Islam, so to realize this, this jargon appears which is then escorted and driven by LP2SI (Institute for the Study and Application of Islamic Shari'ah). Islamic education in this case serves as a reinforcement of the Gate Salam program which then enters all sectors and lines of life of the Pamekasan Regency community both in the realm of implementing formal education and implementing non-formal education. The research method used in this case is to use a qualitative approach with a descriptive type, while the informants in this study are community leaders, public officials who researchers consider to have direct involvement in the formulation of the Gate Greetings program. The research method used in this case is to use a qualitative approach with a descriptive type, while the informants in this study are community leaders, public officials who researchers consider to have direct involvement in the formulation of the Gate Greetings program.